SIGNIFIKANSI PENDIDIKAN MULTIKULTURAL TERHADAP KELOMPOK MINORITAS - Rahim, Rahmawaty (Analisis: Jurnal Studi Keislaman, 2012)
Indonesia as a nation of unity in diversity, composed of various ethnic groups, cultures, religions, social strata and others, is of course, in the hope of  harmony within diversities   in all terms of religion, politics, security, social class and as well as in education  in order to create state social justice and welfare as a reflection of the Pancasila state basis. One way to achieve the above dream is through multicultural education, as a means of building tolerance of ethnic diversity, cultural, and  religion  and  social  strata  of the nation,  because  multicultural education is a response to the diversity of school population growth, as the demand of equal rights for every group. While in the wider sense, multicultural education includes all students regardless of their groups of origins such as religion, gender, ethnic, racial, and cultural, and social strata. Ideally, however, the concept of multicultural education, is not solely directed to the areas of race, religion, and culture. Such a focus  once had been an emphasis  of intercultural  education  that emphasizes  improved  understanding   and  tolerance  of  individuals who come from minority groups integrated into the community of majority. Multicultural  education is actually an attitude of “caring” and willing to understand the discrepancy (difference) or the “politics of recognition”;  political  recognition  of the existence  of the people from minority  groups in all cases and concerns  to achieve  unity in diversity.